Epigenetic Regulation of Embryonic Development: Insights into Congenital Anomalies - Gul Afshan, Muhammad Muneeb Ather, Waqas Iqbal, Muhammad Shakil Sadiq, Ahmad Farzad Qureshi, Asim mehmood, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Epigenetic mechanisms are pivotal in orchestrating embryonic development, and theirdysregulation has been implicated in the etiology of congenital anomalies. This experimental studyaimed to elucidate the role of DNA methylation and histone modification patterns in embryonic